Deconstructing neurobiological coordination: The role of the biomechanics-motor control nexus - Davids, K.; Glazier, P. (Exercise and Sport Sciences Reviews, 2010)
Inherent indeterminacy of neurobiological systems has been revealed by research on coordination of multiarticular actions. We consider three important issues that these investigations raise for biomechanical measurement and performance modeling. These issues highlight the role of dynamic systems theory as a platform for integration of motor control and biomechanics in exercise and sports science.